Efeito da entrada da tubulação por cima do reservatório de jusante nos transientes hidráulicos - Teixeira, Lucas Florêncio da Cunha (2021)
This paper aims at evaluating the effect caused by considering the pipeline connecting through downstream reservoir’s top inlet during hydraulic transient events, presentinga different boundary condition than that classically considered by calculation models. Therefore, a literature review regarding this theme was implemented, exposing the governing equations of transient phenomena, as well as the solution proposed by Method of Characteristics, broadly adopted for one-dimensionaltransient flow solution. Besides, the boundary conditions adopted during this paper’s executionare also shown in the literature review. Then, the used methodology is presented, which makes use of the equations developed by Soares, Covas and Ramos (2013) and the unsteady friction model from Vítkovský et al. (2000)’s work.In order to show the results, this model was implemented into System UFC –Module 7, regarding hydraulic transients’ calculation.For validating the model, the data provided by Soares, Covas and Ramos (2013) was used.For comparison, threemoredistinct pipeline setups were tested.The obtained results show lower positive and negative pressure peaks at the pump section. At the reservoir section, a constant pressure value equal to that from constant reservoir modeling is observed during certain time interval, which varies to each pipeline configuration, and after that the pressure tends to vary and stabilize at a lower value than that from initial steady state. Besides, at this section, a bigger damping in the flow rate happens by considering this boundary condition.Although the classic boundary condition presents a more conservative approach,it does not properly suit the real situation when the pipeline connects through the top inlet of downstream reservoirs, so thelatter is more suitable for maintenance and operation of hydraulic systems that are designed this way.In addition, the simplification of constant downstream reservoir may bring about the hydraulic system’s and protection devices’oversizing, leading to higher design budget.